Targeted metabolites and biological activities of Cydonia oblonga Miller leaves - Oliveira, Andreia P. (2021)
Natural products continue to play a significant role in drug discovery and development processes, and many plants have already provided valuable clues for potentially bioactive compounds. Additionally, in recent years it has become evident that significant health risks and benefits are associated with dietary food choice. Nutritional studies recommend the regular consumption of fruits and vegetables, which constitute an essential part of the Mediterranean diet, to favor a healthy life. Several works have showed that quince tree (Cydonia oblonga Miller) is a good and low cost natural source of metabolites with interesting biological properties. Extensive research has been performed on the metabolic profile and biological potential of this species. In particular, quince leaves revealed to constitute a promising natural source of bioactive phytochemicals, suitable for application in nutritional/pharmaceutical fields. In this review phenolics and organic acids composition of quince leaf is overviewed, as well as its antioxidant and antiproliferative properties, in chemical and cellular in vitro systems. Comparisons with green tea, considered by the scientific community as an effective natural antioxidant, were established.